Solidification/stabilization of landfill leachate concentrate using different aggregate materials - MERTOĞLU, BÜLENT; AKGÜL, DENİZ (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
The application of reverse osmosis for the treatment of landfill leachate is becoming widespread in Turkey as well as in Europe. A major drawback of this process is the production of concentrate, which could be as much as 30% of the feed stream, and high concentrations of salts and contaminants. The reverse osmosis concentrate is disposed of by using several methods including re-infiltration, drying, incineration and solidification/stabilization. In this study, solidification/stabilization (S/S) technology was studied for the treatment of reverse osmosis concentrate produced from landfill leachate. In order to benefit from its capability to absorb heavy metals, ammonia and some other pollutants, zeolite and different aggregate materials were used in solidification experiments. Main pollutants in the leachate concentrate, TOC, DOC, TDS and ammonia were successfully solidified and approximately 1% of TOC, DOC, TDS and ammonia remained in the eluate water. The results indicated that the landfill disposal limits could be attained by solidification/stabilization process. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Leachate; Reverse osmosis; Concentrate; Solidification/stabilization; Zeolite; ARC FURNACE DUST; ZEOLITE